An Exploration of Private Sector Financing of Higher Education in the Philippines and Its Policy Implications for India - M. JOSHI K. (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The private higher education sector of the Philippines is proportionally one of the largest in the world. It is the only system where proprietary institutions also assume importance along with the sectarian not-for-profit institutions, and their behaviour appears parallel, which works on the rules of the market. The private higher education sector of the Philippines has a long history, which can be traced from the Spanish regime. It grew largely in the post independence period in the absence of resources of the state for higher education along with any precise policy. The private sector received further impetus through the growing private demand. A closer look at the functioning of these institutions reveals that they heavily rely upon tuition revenues, predominantly upon a student client that is by no means healthy. The private higher education institutions have failed to trap other private resources. These institutions also have a wide disparity in terms of quality, from lowest to the highest. Although there exists the private and state scholarships, but the equity issue still appears to be unattended in true sense, and are affected by quality of institutions, location, tuition fees and economic background. In spite of these demerits the transition rate between secondary and higher education in Philippines remains exceptionally high, along with the participation ratio, which is comparable to a developed nation. It is the presence of this private sector that has made the higher education accessible in terms of increased participation, in absence of state resources. The present study in context of the Philippine private higher education tries looks at the history, distinguishing characteristics, and examines the issues of equity, efficiency and quality in order to bring out some policy implications for the emerging private higher education system of India